The management of school coexistence in basic education in Mexico: From the perspective of educational marketing - Larios Gómez, Emigdio (2021)
The objective of the work was to evaluate the Perceived School Climate (school and classroom) in the Amozoc de Mota secondary school (Puebla, Mexico) from an educational marketing perspective. It was developed a conclusive-descriptive and transversal research, surveying 215 teachers with an instrument adapting the constructs on the Study of behaviors, climate and school coexistence. Likewise, the analysis of the school environment was carried out by surveying 150 students. In the results analyzed, it was observed that the secondary school teacher does not perceive support or feel valued by his peers and directors, which generates a complex work environment and influences a difficult management for school coexistence. It was concluded that the teacher is an agent of scaffolding in the school climate, allowing the establishment of an instructional space in the classroom and the construction of learning with positive ties, a cordial and safe climate with rules and limits. Likewise, it promotes in the students the personal, social, academic and cognitive development-learning for life. In addition, the role of the teacher within the classroom is of paramount importance in the classroom climate perceived by the students. Students feel good about each other, accepted and respected based on the teacher's conciliatory, intervening and authoritative stance. This is where Educational Marketing comes in and can help improve coexistence and promote relationships based on respect and acceptance. This will develop in students, teachers, managers and parents assertive and critical attitudes, with values and analytical awareness.